2019
DOI: 10.1021/acsomega.9b04009
|View full text |Cite
|
Sign up to set email alerts
|

(Diacetoxyiodo)benzene-Mediated C–H Oxidation of Benzylic Acetals

Abstract: A useful oxidation of C–H bond of benzylic acetals has been achieved. This method avoids the use of stoichiometric metals and is compatible with the presence of both electron-donating and electron-withdrawing substituents on the aromatic ring. Oxidation was carried out by rapid microwave irradiation of benzylic acetals with PhI­(OAc)2 as the oxidant. This led to the oxidation of acetals into 2-acetoxy-1,3-dioxolanes. Furthermore, this transformation protocol encompasses a wide range of valuable conversions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, when we carried the reaction out in the absence of HAuBr 4 under aerobic conditions we observed alcohol and ketone products alongside a significant amount of acetoxylated products. The acetoxylation of C(sp 3 )−H in benzylic acetals using PhI(OAc) 2 has indeed been reported [16] . Removal of oxygen almost fully prevented this.…”
Section: Methodsmentioning
confidence: 72%
“…However, when we carried the reaction out in the absence of HAuBr 4 under aerobic conditions we observed alcohol and ketone products alongside a significant amount of acetoxylated products. The acetoxylation of C(sp 3 )−H in benzylic acetals using PhI(OAc) 2 has indeed been reported [16] . Removal of oxygen almost fully prevented this.…”
Section: Methodsmentioning
confidence: 72%
“…[117] At room temperature, the process was carried out in an aerobic environment. Under the circumstances of this reaction, many aryl-2H-azirines (110) produced the corresponding acyloxylated azirines (111). The process of the reaction involved radicals.…”
Section: Chemistryselectmentioning
confidence: 99%
“…The α-oxidation of aromatic ketones in this study was reported by Zhang and co-workers (Scheme 31). [111] Optimized conditions: PIDA (2 equiv. ), Pd(OAc) 2 (5 mol %) in AcOH at120 °C under nitrogen atmosphere.…”
Section: Acetoxylation/acetalization/alkoxylationmentioning
confidence: 99%
See 1 more Smart Citation
“…12−16 To achieve the green, safe, and low-cost oxidation of the C−H bond, researchers have begun to explore new reaction systems, such as photochemical oxidation, 17 electrochemical oxidation, 18,19 and microwave oxidation. 20 Selective electrochemical oxidation of the C−H bond provides a green and environmentally compatible method using cost-effective electricity under mild conditions with high atom economy. 21−25 These advantages originate from the electrons employed as oxidants, adjustable oxidation potential, and the use of sustainable electricity, avoiding the harsh operating conditions and toxic oxidants.…”
Section: Introductionmentioning
confidence: 99%